Lifestyle modifications and nonpharmacological interventions to improve outcomes in psoriatic arthritis. A systematic review - Hailey, LH; Amarnani, R; Bundy, C; McGagh, D; James, L; Kirtley, S; O'Sullivan, D; Steinkoenig, I; Suribhatla, R; Vivekanantham, A; Coates, LC (Elsevier, 2023)
Purpose Psoriatic arthritis (PsA) is a multisystem inflammatory disorder associated with significant mortality and morbidity, including functional impairment and psychological disability. Although evidence-based treatment recommendations are available for the use of drug treatments in PsA, there is little guidance for health professionals on nonpharmacologic and psychological interventions that may be useful in PsA. The objective of this systematic review (SR) was to identify how lifestyle modifications and the use of nonpharmacologic and psychological interventions may improve the outcomes of patients with PsA. Methods Studies were included if they evaluated adults diagnosed with PsA and included exposure to nonpharmacologic interventions, psychological interventions, and lifestyle modifications. The outcomes used needed to have been validated in PsA. A systematic literature search was run on May 28, 2021, in the Cochrane Central Register of Controlled Trials (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Allied and Complementary Medicine Database (AMED), EMBASE, Global Health, MEDLINE, and PsycINFO databases to identify articles related to lifestyle modifications and nonpharmacologic or psychological interventions for adults with PsA published between 2010 and 2021. Two review authors independently screened and selected full-text studies for inclusion in the SR. Risk of bias was assessed with either the Risk of Bias 2 (ie, RoB 2) tool or Critical Appraisal Skills Program checklist depending on the study type. Findings The search strategy identified 26,132 references. Eight studies examining lifestyle modifications and the effect on PsA were eligible to be included in the SR. Three of the 8 studies were randomized controlled trials, and 5 were nonrandomized studies. Three studies assessed physical activity, 3 assessed diet, 1 study assessed smoking, and another study assessed mud bath therapy. There was large heterogeneity between studies, and the measures of disease activity, and psychological and functional outcomes varied widely between studies. Implications Although this SR identified 8 relevant studies, these studies did not provide high-quality evidence to guide patients for non-drug treatments of PsA. The effectiveness of these interventions has therefore not been established. We found that physical activity seems to have a positive impact on disease activity and psychological well-being. Further well-designed research studies are needed to develop treatment recommendations. PROSPERO identifier: CRD42021257404.